Trends and projections of universal health coverage indicators in China, 1993-2030: An analysis of data from four nationwide household surveysResearch in context - Yuanyuan Li; Chunfeng Zhang; Peng Zhan; Hongqiao Fu; Winnie Yip (Elsevier, 2023)
Summary: Background: Universal health coverage (UHC) is a core element of Sustainable Development Goals and has become a global healthcare priority. China has been committing to provide all citizens with affordable and equitable basic healthcare over past decades. However, progress towards UHC in China has not been comprehensively assessed. This study aims to comprehensively evaluate the progress towards UHC in China by examining trends in service coverage and financial protection from 1993 to 2018, and estimating the probability of achieving UHC targets by 2030. Methods: Following the framework proposed by World Health Organization and World Bank, we selected 12 prevention service indicators, 12 treatment service indicators, and two financial protection indicators to evaluate China's progress towards UHC. We used data from four nationally representative household surveys to assess the trends in service coverage and financial protection between 1993 and 2018, as well as their inequalities across subgroups. Meta-analysis was used to construct the composite prevention and treatment indices. The regression-based relative index of inequality was used to measure the income-related inequality of UHC indicators. Bayesian linear regression was conducted to predict progress towards UHC by 2030, and the probability of achieving UHC targets. Findings: Of the 24 service coverage indicators used in this study, most of them experienced improvements between 1993 and 2018. The composite prevention index increased from 65.6% (95% CI: 52.1%-77.9%) to 87.7% (95% CI: 81.8%-92.6%) and the composite treatment index increased from 57.1% (95% CI: 43.5%-70.1%) to 75.5% (95% CI: 66.6%-83.5%). The inequalities of service coverage experienced significant declines during this period. Based on our projections, most indicators except ones in the area of non-communicable diseases (NCD) will achieve the 80% coverage target by 2030, and the prevention and treatment indices will increase to 92.7% (95% CrI: 90.3%-94.7%) and 83.2% (95% CrI: 75.1%-88.8%) by then. However, we observed limited reductions in the incidences of catastrophic health expenditure and medical impoverishment. Inequalities in financial protection remained large in 2018. Interpretation: China had made significant progress in improving healthcare service coverage and reducing inequalities between 1993 and 2018. However, China faces great challenges in improving financial protection and controlling NCD on its path towards UHC. Establishment of a primary-healthcare-based integrated delivery system and provision of better financial protection for vulnerable population should be prioritized. Funding: None.